The Rainbow. - Lawrence, D. H. (David Herbert), 1885-1930. (London : Penguin, 1998)
Lawrence's classic novel chronicles the lives of three generations of the Brangwen family in Nottinghamshire. Increasingly, the story focuses on Ursula, and follows her development through adolescence and early womanhood.
Keywords: Midlands (England) -- Social life and customs -- Fiction